Development of a prototype mechanical road cleaning machine / Muhammad Syafiq Bahrin - Bahrin, Muhammad Syafiq (2023)
Cleaning is a necessary factor of daily routine process. Effective cleaning and sanitizing help and protect the health of human beings directly and indirectly. The Road cleaner is used to keep our surroundings clean. So that we feel fresh while walking on the streets. My objective of this project is to design and analysis a Mechanical Road Cleaner Machine and to fabricate an affordable and functional Mechanical Road Cleaner Machine. The problem that most users faced is most of the road cleaning machine nowadays is expensive, hard to be operated and not a user friendly. Other than that, most of that machine also take time and cost to be operated because they use a power supply that need to recharge and refuel. So, in my project I will try to make an affordable and a machine that is easy to maintain. The expected result is to make a functional road cleaning machine for the user. In conclusion, I hope my project will solve all the problems that usually a user faced